Marital privilege: Bias against divorced patients in medical decision-making. - Marotta, Satia.; Ladin, Keren. (Tufts University. Tisch Library., 2019)
Social support consists of the emotional, informational, and instrumental resources we receive from others, and buffers against negative health outcomes. However, as an eligibility criterion for scarce medical resources, such as organ transplants, it can be vague, subjective, and vulnerable to bias. In three studies, we examine bias associated with marital status, and assess whether those with nonspousal relationships with their caregivers (e.g., divorcees) and those without documented primary caregivers experience bias in transplant listing evaluations. We found evidence of bias against those with nonspousal relationships with their caregivers. Divorced patients were perceived as having less durable and adequate social support than those who were married to their caregivers. Divorced patients were also perceived as less deserving of a transplant and were less likely to be recommended for transplant wait-listing. Recommendations for avoiding bias in social support evaluations are discussed.